Video-Mediated Physics Instruction From Preservice Teachers to Elementary Students: Experiences and Reflections. Issue 2 (3rd April 2018) - Laherto, Antti; Laherto, Jussi
Abstract: Addressing the widely reported deficiencies in elementary teachers' competence in technology use and in inquiry-based science instruction, we present and assess a novel teaching experiment conducted in a university–school collaboration. Preservice elementary teachers planned and produced teaching videos in which they gave instructions on experimental work to a class of 11-year-old pupils. Pupils watched the videos, carried out the experiments, and videoed their feedback to the preservice teachers. In their qualitative and quantitative questionnaire responses, the preservice teachers ( n = 130) reported having learned broadly about physics concepts, experiments, pupils' conceptions and abilities, and the use of information and communication technology (ICT) in teaching and learning. We discuss the detected benefits, problems, and potential of video-mediated instruction of real-life student work in preservice teacher education. (Keywords: ICT in education, physics teaching, preservice elementary teacher education, student content creation, video production)